1997
DOI: 10.1128/jvi.71.1.50-58.1997
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent regulation of the early promoter of human papillomavirus type 18 by the viral E2 protein

Abstract: The activity of the E6/E7 promoter of genital human papillomaviruses (HPVs) is positively and negatively modulated by a complex interplay between a variety of cellular transcription factors and the virally encoded E2 protein. The long control region of genital HPVs contains four E2 binding sites in conserved positions, two of which are very close to the TATA box. Binding of E2 to these two sites has been shown to repress the promoter. To carefully analyze the effect of E2 on the activity of the early promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
1
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(68 citation statements)
references
References 49 publications
4
59
1
4
Order By: Relevance
“…Mutation of all three promoter-proximal E2 BS fully relieved E2-mediated repression of P 105 transcription and led to a three-to sixfold activation of transcription. This activation probably depends on the binding of E2 to E2 BS 4 as recently suggested (32). We thus confirmed that E2-mediated repression was dependent only on the integrity of E2 BS 1 in C33 cells while it required two additional binding sites (E2 BS 2 and 3) in HeLa and HaCaT cells.…”
Section: Resultssupporting
confidence: 89%
“…Mutation of all three promoter-proximal E2 BS fully relieved E2-mediated repression of P 105 transcription and led to a three-to sixfold activation of transcription. This activation probably depends on the binding of E2 to E2 BS 4 as recently suggested (32). We thus confirmed that E2-mediated repression was dependent only on the integrity of E2 BS 1 in C33 cells while it required two additional binding sites (E2 BS 2 and 3) in HeLa and HaCaT cells.…”
Section: Resultssupporting
confidence: 89%
“…With consequently rising concentrations, E2 also binds to the lowaffinity proximal E2BS3 and E2BS4. This represses transcription from the p97 promoter and thereby maintains the levels of E6 and E7 at a low and autoregulated level as shown in Figure 1A 9,10,12 and as reviewed by von Knebel Doeberitz and Vinokurova 11 (note that the numbering of E2BSs in the study by von Knebel Doeberitz and Vinokurova 11 differs from that currently used).…”
Section: Introductionmentioning
confidence: 92%
“…7 The most important transcriptional regulator of E6 and E7 oncogene expression is the viral E2 protein, which binds to 4 E2-binding sites (E2BSs1, 2, 3, and 4) in the URR. 8 The current model of E2 function in the host cells during the normal viral life cycle implies that E2 binds with high affinity to the E2BS1, resulting in activation of the p97 early promoter even at low E2 concentrations, 9,10 as reviewed by von Knebel Doeberitz and Vinokurova. 11 This promoter activation results in enhanced expression of the early viral proteins, including the oncoproteins E6 and E7 and E2 itself.…”
Section: Introductionmentioning
confidence: 99%
“…If the concentration of the E2 protein rises beyond a certain level, E2 binds also to the low affinity proximal E2BSs (E2BS2, 3 and 4) and represses transcription from the early promoter p97 through displacement of Sp1 and TBP from their respective binding sites, thereby keeping the levels of E6 and E7 under control. [11][12][13] Accordingly, it has been suggested that deregulated expression of E6 and E7 oncogenes and initiation of the transformation process may result from loss of the E2 repressive functions. Viral integration into the host genome usually occurs downstream of the E6 and E7 genes, often in E1 and E2 regions 14,15 and results in a loss of negative-feedback control of oncogene expression.…”
mentioning
confidence: 99%